THE APPLICATION OF LANDSAT IMAGERY PROCESSING FOR EROSION STUDY - Sukiyah, Emi; Fachrudin, Kurnia Arfiansyah (Journal of Geological Sciences and Applied Geology, 2021)
Landsat imagery has a relatively smaller resolution than topographic maps, within certain limits it can support the morphometric analysis of a watershed. The results of the average difference test between the drainage density population from Landsat imageries and topographic maps, at a significant level of 0.20, are proven to be significant. In certain cases, its value can reflect the effectiveness of erosion in an area. For relatively supportive bedrock types, it is can reflect the erodibility of soil from weathering the bedrock. Combination of fit some bands of Landsat Images can appear unique tones and features. They can lead for erosion zones delineation. Thus phenomena reflected by various scatter gram patterns. The range of digital number can reflect erosion grade by ratio analysis of band 1- band 4 and band 1- band 7. The phenomenon shows that Landsat imagery can be used for delineation of erosion zones based on the characteristics of the earth's surface constituent materials through digital number range analysis.